Using cluster analysis to identify the health literacy strengths and challenges of people living with motor neurone disease in Australia - Arabelle Douglas; Maryanne McPhee; Fiona Fisher; Christina Cheng; Anjali Henders; Laura Ziser; Julie C. Stout; Matthew C. Kiernan; Richard Osborne; Susan Mathers (BMC Health Services Research)
Abstract Background There is growing appreciation of the role health literacy plays in population health and health care design. Health literacy encompasses an individual’s capacity to manage their health and the responsiveness of the health system. Our aim was to identify the health literacy strengths and challenges in an Australian cohort living with motor neurone disease (MND), including both people living with the disease and their carers. Methods This study used the Health Literacy Questionnaire and eHealth Literacy Questionnaire for health literacy assessment. Using a secure online platform, an anonymous survey was disseminated which included demographic data and clinical measurements. Descriptive statistical analysis and cluster analysis were employed to describe the sample and to identify different health literacy patterns in subgroups of people living with MND and their carers. Results A total of 227 people participated (171 people living with MND and 56 carers). Cluster analysis generated fifteen cluster profiles for the cohort living with MND and seven cluster profiles for carers. The variability and potential significance of patterns of health literacy strengths and challenges within the MND community are described. There was extensive diversity within the sampled population, with a mix of sociodemographic backgrounds across each cluster profile. Conclusions The health literacy cluster profiles created from this study provide insight into the full spectrum of where the challenges and strengths exist for individuals and subgroups of people managing this fatal disease. The results from this study pave the way for generating system wide interventions that address health literacy diversity, to create more enabling health care environments for all those affected by MND.